2022
DOI: 10.1038/s41591-022-02046-0
|View full text |Cite
|
Sign up to set email alerts
|

Rare and common genetic determinants of metabolic individuality and their effects on human health

Abstract: Garrod’s concept of ‘chemical individuality’ has contributed to comprehension of the molecular origins of human diseases. Untargeted high-throughput metabolomic technologies provide an in-depth snapshot of human metabolism at scale. We studied the genetic architecture of the human plasma metabolome using 913 metabolites assayed in 19,994 individuals and identified 2,599 variant–metabolite associations (P < 1.25 × 10−11) within 330 genomic regions, with rare variants (minor allele frequency ≤ 1%) explaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
74
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 75 publications
2
74
0
1
Order By: Relevance
“…Our finding that the effect of finasteride on suicidal risk, if any, would be more apparent in people with a history of mood disorders suggests that finasteride alone is unlikely to facilitate a suicidal act. Of note, a recent study found genetic evidence that inhibition of 5α-reductase was associated with depression 56 . However, for reasons largely unknown at this stage, finasteride may further trigger a suicidal act in those who are already in a fragile mental state or at-risk to be in such a mental state.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that the effect of finasteride on suicidal risk, if any, would be more apparent in people with a history of mood disorders suggests that finasteride alone is unlikely to facilitate a suicidal act. Of note, a recent study found genetic evidence that inhibition of 5α-reductase was associated with depression 56 . However, for reasons largely unknown at this stage, finasteride may further trigger a suicidal act in those who are already in a fragile mental state or at-risk to be in such a mental state.…”
Section: Discussionmentioning
confidence: 99%
“…The standard genome-wide significance threshold was Bonferroni corrected for the number of independent bile acid traits, calculated as 14 (5x10 -8 /14 = 3.57x10 -9 ). The number of independent bile acid traits was estimated as the sum of the number of binary traits (4) and the number of principal components that jointly explained 99% of the total variance of log10transformed quantitative traits in each cohort (10) (Supplementary Table 13).…”
Section: Meta-analysismentioning
confidence: 99%
“…While many studies have focused on the genetic determinants of blood metabolites [10][11][12][13][14][15] , research focusing specifically on bile acids in a large sample from the general population is currently lacking. Here we investigate the genetic architecture of primary and secondary BAs, reporting associations with both common and low-frequency/rare variants.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, four studies on the potential value of small-molecule metabolites by high-throughput functional metabolomics were published in Nature Medicine ( Buergel et al, 2022 ; Chen et al, 2022 ; Kachroo et al, 2022 ; Surendran et al, 2022 ). These studies have shown that metabolic profiling of small molecules offers invaluable insights into the function of candidate metabolites, leading to better diagnosis, prognosis, and therapeutic effects.…”
mentioning
confidence: 99%
“…This study showed that the great potential of metabolic profiling can provide comprehensive and accurate pictures of phenotypes related to various diseases or drug monitoring. A snapshot of human metabolism was also revealed by Surendran et al (2022) , and untargeted high-throughput metabolomics identified a total of 2,599 metabolite-specific associations in 19,994 individuals and provided insights into metabolite function and drug effects.…”
mentioning
confidence: 99%